The book of Deuteronomy, chapters 1-11 - Arnold, Bill T. 1955- (William B. Eerdmans Publishing Company, 2022)
"A commentary on the book of Deuteronomy that explores both the book's historical context and its meaning and use as Christian Scripture today"--
Keywords: Bibel -- Deuteronomium -- 1-11; Bible / Deuteronomy, I-XI / Commentaries; RELIGION / Biblical Commentary / Old Testament / Pentateuch; RELIGION / Biblical Studies / Old Testament / Pentateuch; Commentaries; Kommentar